2023
DOI: 10.1108/lhtn-11-2022-0125
|View full text |Cite
|
Sign up to set email alerts
|

Use of artificial intelligence in the library services: prospects and challenges

Abstract: Purpose Artificial intelligence (AI) is one of the emerging technologies of this time. It has been associated with several trades like business, defense, health and education, but its role in library services will foster intelligent decisions. AI is a widely used technology in library services that can transform the best services in the age of information technology. This paper aims to highlight the use of AI in library operations. Several research have been undertaken on this subject, but that only address a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 14 publications
2
32
0
3
Order By: Relevance
“…According to Hussain (2020aHussain ( , 2020b; Ali et al (2020), it has been observed that in developing countries, many librarians remain unaware of the potential deployment of AI within their libraries. This lack of awareness could be attributed to a combination of limited knowledge and the substantial financial investment associated with implementing AI in library services.…”
Section: Challenges In Implementing Artificial Intelligence In Librar...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hussain (2020aHussain ( , 2020b; Ali et al (2020), it has been observed that in developing countries, many librarians remain unaware of the potential deployment of AI within their libraries. This lack of awareness could be attributed to a combination of limited knowledge and the substantial financial investment associated with implementing AI in library services.…”
Section: Challenges In Implementing Artificial Intelligence In Librar...mentioning
confidence: 99%
“…Libraries have long been considered as repositories of knowledge and information and have been playing a crucial role in providing access to resources and facilitating learning for individuals from all walks of life. In an increasingly digital world, libraries face the challenge of adapting to changing user needs and expectations (Hussain, 2023). This necessitates embracing technological advancements to enhance their services and remain relevant in today’s society.…”
Section: Introductionmentioning
confidence: 99%
“…The same platform will be used for reader communication, and readers will have cheaper availability of humanized services. A few academics, such as Hussain (2020aHussain ( , 2020b, noted that most librarians in underdeveloped nations are still ignorant of its deployment in their libraries. Perhaps this is due to a lack of knowledge or the high cost of integrating AI into library services.…”
Section: Artificial Intelligence and Librariesmentioning
confidence: 99%
“…The application of AI in libraries will lead to favorable changes in how the work is carried out. In the era of the information explosion, AI in library services will give users access to reliable information and serve as a useful tool for the natural integration of readers and libraries (Hussain, 2023). AI can be simply implemented in technical services of the library like categorization and cataloguing, library management tasks like staffing and decision-making, library services like referencing and information service and information literacy, all can benefit from the adoption of AI in libraries and information centers (Harisanty et al , 2023).…”
Section: Artificial Intelligence and Librariesmentioning
confidence: 99%
“…For this, library personnel will need a solid understanding of AI technologies and the ability to use them in their work. Many libraries and information services already use AI in their operations (Alam, 2022; Hussain, 2023). In particular, machine learning technologies are being used for activities like automatic resource categorization and classification; collection recognition and weeding; automated cataloguing and data entry; personalized suggestions based on users’ search and lending histories and other data (Cordell, 2020; Gul and Bano, 2019; Pekala, 2017; Yang, 2022); and the application of voice assistants, virtual assistants and chatbots to educational institutes’ library services (Mckie and Narayan, 2019).…”
Section: Introductionmentioning
confidence: 99%